Pre-incubation of porcine semen reduces the incidence of polyspermy on embryos derived from low quality oocytes - Brogni,Cláudio Francisco (2016)
ABSTRACT: The main cause of low efficiency of in vitro produced porcine embryos is the high polyspermic penetration rates at fertilization, which is aggravated in low quality oocytes. Experiment 1 evaluated the embryo development in high and low quality oocytes. Experiment 2 evaluated the embryo development and quality of low quality oocytes fertilized with sperm pre-incubated during 0h (control), 0.5h, 1h and 1.5h. Experiment 3 investigated fertilization and monospermic rates of the same groups of Experiment 2. Experiment 4 evaluated embryo development, cell density, fertilization and monospermic rates of high quality oocytes using semen pre incubated during the best time observed in the previous experiments. Cleavage and blastocyst rates were analyzed by chi-square test, and remaining data by ANOVA and Tukey test (P≤0.05). The cleavage (74.8 vs 51.7%) and blastocyst (33.7 vs 9.8%) rates were greater in oocytes of high versus low quality, with no differences in cell density. Fertilization rates (65.6 to 79.5%) were not influenced by pre-incubation time. However, semen pre-incubation during 1.5h increased monospermic penetration (53.3%) and cleavage rates (92.5%) in low quality oocytes. Blastocyst rate was improved with 1.5h of semen pre incubation; however they were still lower than that observed with high quality control oocytes. Ultimately, pre-incubation did not influence fertilization, monospermic penetration, embryo development rates, nor cell density in oocytes of high quality. Low-quality porcine oocytes resulted in better rates of embryo development if in vitro fertilized with sperm pre-incubated for 1.5 hour.